THE IMPORTANCE OF MUSIC EDUCATION IN SECONDARY SCHOOLS (American Journal of Interdisciplinary Research and Development, 2025)
The article deals with the science of music in education, how important music lessons are in schools and the purpose of teaching music to students. The impact and benefits of music for schoolchildren and recommendations for music teachers.